Menu Close

Question-167594




Question Number 167594 by infinityaction last updated on 20/Mar/22
Answered by som(math1967) last updated on 20/Mar/22
cosx+cosy+cosz=pcos(x+y+z)  cosxcos(x+y+z)+cosycos(x+y+z)  +coszcos(x+y+z)=pcos^2 (x+y+z)  ........case  i)  same way  sinxsin(x+y+z)+sinysin(x+y+z)  +sinzsin(x+y+z)=psin^2 (x+y+z)  .......case ii)  casei)+caseii)  cosxcos(x+y+z)+sinxsin(x+y+z)  +cosycos(x+y+z)+sinysin(x+y+z)  coszcos(x+y+z)+sinzsin(x+y+z)  =p{sin^2 (x+y+z)+cos^2 (x+y+z)}  cos(x+y+z−x)+cos(x+y+z−y)  +cos(x+y+z−z)=p×1  ∴cos(x+y)+cos(y+z)+cos(z+x)=p
cosx+cosy+cosz=pcos(x+y+z)cosxcos(x+y+z)+cosycos(x+y+z)+coszcos(x+y+z)=pcos2(x+y+z)Missing or unrecognized delimiter for \leftsamewaysinxsin(x+y+z)+sinysin(x+y+z)+sinzsin(x+y+z)=psin2(x+y+z)Missing or unrecognized delimiter for \leftcasei)+caseii)cosxcos(x+y+z)+sinxsin(x+y+z)+cosycos(x+y+z)+sinysin(x+y+z)coszcos(x+y+z)+sinzsin(x+y+z)=p{sin2(x+y+z)+cos2(x+y+z)}cos(x+y+zx)+cos(x+y+zy)+cos(x+y+zz)=p×1cos(x+y)+cos(y+z)+cos(z+x)=p

Leave a Reply

Your email address will not be published. Required fields are marked *